2020
DOI: 10.36129/jog.32.02.04
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization and psychological stress: new insight about different routes of progesterone administration

Abstract: Infertility treatment is a stressful process and factors like anxiety and preoccupation could affect the success of In Vitro Fertilization (IVF) or other assisted reproductive techniques. Moreover, luteal phase support (LPS) in IVF cycles is recommended. Our aim was to analyze the effects of LPS with intramuscular and subcutaneous progesterone on stress hormones (cortisol and prolactin). We analyzed one hundred-thirty women undergoing their first IVF cycle and then randomized in two groups: group A (65 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A comparison between the intramuscular and subcutaneous routes was recently carried out by Mele et al in 2020 ( 30 ). In detail, 130 women undergoing a first IVF cycle were randomized to intramuscular Pg (33 mg/day from ovum pick up and 50 mg/day from embryo transfer) and subcutaneous Pg (25 mg/day).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison between the intramuscular and subcutaneous routes was recently carried out by Mele et al in 2020 ( 30 ). In detail, 130 women undergoing a first IVF cycle were randomized to intramuscular Pg (33 mg/day from ovum pick up and 50 mg/day from embryo transfer) and subcutaneous Pg (25 mg/day).…”
Section: Resultsmentioning
confidence: 99%
“…Subcutaneous administration can be self-administered and is associated with lower injection site reactions, such as pain and irritation, compared with the intramuscular route ( 28 ). In addition, Mele et al reported a significantly reduced level of stress-related hormones, such as Prolactin and Cortisol ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Points to be considered when determining a treatment plan include location, size and gestational age of the pregnancy, the hemodynamic stability and desire for future fertility [11]. Moreover, when dealing with fertility desire a careful consideration must be posed for possible psychological distress of the couple [15,16]. The various modalities for the management of CSP include conservative management, medical termination with methotrexate, uterine artery embolization (UAE) and surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a shortage of donors in many countries [9] and the selection of a suitable donor has become a challenge for infertile couples due to the mismatch between supply and demand [10]. Sometimes the demand for donated oocytes exceeds the supply in many countries around the world [9][10][11].…”
Section: Introductionmentioning
confidence: 99%